The loading rate effect on Mode II fracture toughness of composites interleaved with CNT. Issue 1 (2nd January 2016) - Lyashenko-Miller, T.; Fitoussi, J.; Marom, G.
Abstract: The loading rate effect on Mode II interlaminar fracture toughness (ILFT) is examined in this study with interleaved epoxy/carbon fabric laminates tested under dynamic conditions. Specifically, an SP1 protein-treated carbon nanotube-reinforced epoxy leaf is inserted at the midplane of the laminates, and the fracture properties are measured by the crack lap shear method at two different loading rates. Whereas our preliminary study performed under quasi-static conditions showed that this specific interleaving generated an 85% improvement in the Mode II ILFT, the current work shows that the occurrence and magnitude of the improvement depend on the loading rate and crack velocity, with different effects on the initiation and the instable/stable propagation stages. Improvements in Mode II ILFT for both the crack initiation and propagation phases can reach up to 145% for certain dynamic loading conditions. Graphical abstract: